Causes of preventable drug-related hospital admissions: a qualitative study. Issue 2 (2nd April 2008) - Howard, R; Avery, A; Bissell, P
Abstract : Objective: To explore the causes of preventable drug-related admissions (PDRAs) to hospital. Design: Qualitative case studies using semi-structured interviews and medical record review; data analysed using a framework derived from Reason's model of organisational accidents and cascade analysis. Participants: 62 participants, including 18 patients, 8 informal carers, 17 general practitioners, 12 community pharmacists, 3 practice nurses and 4 other members of healthcare staff, involved in events leading up to the patients' hospital admissions. Setting: Nottingham, UK. Results: PDRAs are associated with problems at multiple stages in the medication use process, including prescribing, dispensing, administration, monitoring and help seeking. The main causes of these problems are communication failures (between patients and healthcare professionals and different groups of healthcare professionals) and knowledge gaps (about drugs and patients' medical and medication histories). The causes of PDRAs are similar irrespective of whether the hospital admission is associated with a prescribing, monitoring or patient adherence problem. Conclusions: The causes of PDRAs are multifaceted and complex. Technical solutions to PDRAs will need to take account of this complexity and are unlikely to be sufficient on their own. Interventions targeting the human causes of PDRAs are also necessary—for example, improving methods of communication.